2011
DOI: 10.3928/00220124-20110315-03
|View full text |Cite
|
Sign up to set email alerts
|

Reflecting on Research: Sharpening Nurses’ Focus Through Engaged Learning

Abstract: Participating in the Bedside Scientist Institute was transformative. The course opened participants' minds to question traditional practice, developing champions for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…However, the most common intervention mentioned in the literature for improving research utilization is education. Several authors describe educational programs and activities to enhance research knowledge and skills of knowledge translation [6,[13][14][15][16][17] as a form of organizational support for evidencebased practice [18,19]. These educational interventions are thought to strengthen research competencies [19,20] and provide research literacy, understanding of the literature, critical assessment of research findings and confidence in decision-making on the clinical usefulness of evidence [21].…”
Section: Interventions and Activities To Develop Nurse Researcher Commentioning
confidence: 99%
“…However, the most common intervention mentioned in the literature for improving research utilization is education. Several authors describe educational programs and activities to enhance research knowledge and skills of knowledge translation [6,[13][14][15][16][17] as a form of organizational support for evidencebased practice [18,19]. These educational interventions are thought to strengthen research competencies [19,20] and provide research literacy, understanding of the literature, critical assessment of research findings and confidence in decision-making on the clinical usefulness of evidence [21].…”
Section: Interventions and Activities To Develop Nurse Researcher Commentioning
confidence: 99%
“…8 Interventions that improved attitudes were EBP/research councils, 9 journal clubs, 14 critical appraisal seminars, 10 EBP workshops with co-interventions like opinion leaders, 5 or formal immersion programs. 6,12,13 Qualitative evidence confirmed that educational programs opened nurses' minds about the value that research brings to practice. Nurses expressed broadened worldviews and renewed empowerment and accountability to question and reflect on their practice.…”
Section: Resultsmentioning
confidence: 89%
“…Nurses expressed broadened worldviews and renewed empowerment and accountability to question and reflect on their practice. [12][13][14] For knowledge and skills, written instructions assisted clinicians in developing correct PICO questions. 5 One-day seminars significantly increased critical appraisal knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…A recent evidence synthesis reported 10 studies evaluating the effectiveness of educational interventions in building EBP attitudes, knowledge, skills, and behaviors of nurses (Halm, ). Interventions were primarily workshop or immersion programs, but seminars, journal clubs, and EBP and research councils were also evaluated via: (a) self‐reported EBP attitude, knowledge, and behavior (Chang et al., ; Dizon, Somers, & Kumar, ; Edward & Mills, ; Leung, Trevana, & Waters, ); (b) PICO questions and activity diaries (Dizon et al., ); (c) Edmonton Research Orientation (Gardner, Smyth, Renison, Cann, & Vicary, ) and Clinical Effectiveness or EBP Questionnaire (Sciarra, ; Toole, Stichler, Ecoff, & Kath, ; White‐Williams et al., ); and (d) interviews and focus groups to identify qualitative themes about nurses’ experience in EBP programs (Balakas, Sparks, Steurer, & Bryant, ; Nesbitt, ; Wendler, Samuelson, Taft, & Eldridge, ). Varied measurement across studies limited estimation of the effectiveness of EBP training (Dizon et al., ).…”
Section: Introductionmentioning
confidence: 99%